Clinical findings, treatment, and outcomes in cats with naturally occurring hypoadrenocorticism: 41 cases - Emma Roberts; Ian K. Ramsey; Ruth Gostelow; Anna Latysheva; Luca Battaglia; Paolo Silvestrini; Ghita Benchekroun; Karen Brenner; Bérénice Conversy; Riccardo Ferriani; Andre Kortum; Lisa Stammeleer; et al. (Journal of Veterinary Internal Medicine)
Abstract Background Hypoadrenocorticism in cats is uncommonly reported. Most reports consist of cats with hyponatremia, hyperkalemia, or both. Hypothesis/Objectives To describe clinical findings, treatment response, and outcome in cats diagnosed with hypoadrenocorticism, including cats with abnormal and normal serum sodium and potassium concentrations. Animals Forty‐one cats with hypoadrenocorticism; 36 with and 5 without abnormal serum sodium and potassium concentrations. Methods Multicenter retrospective observational study. Data for the entire cohort were assessed using descriptive statistics and differences between cats with and without abnormal serum sodium and potassium concentrations were evaluated. Results Median age was 5.7 years (range, 0.2‐13.8). Twenty‐three (56%) cats were male and 18 (44%) were female. Cats with hyponatremia, hyperkalemia, or both were less likely to have a history of vomiting (P = .01) but more likely to be hypothermic (P = .03), dehydrated (P = .04) or weak (P = .04) on examination, compared with nonhyponatremic and nonhyperkalemic cats. Frequency of hypercalcemia was 31.7%. Exocrine pancreatic insufficiency (EPI) was diagnosed in 4/7 cats tested; all 4 had concurrent cobalamin deficiency. Thirty‐five (85.4%) cats survived to discharge. In 2 cats, hypoadrenocorticism occurred secondary to lymphoma. Median survival time (MST) for all‐cause mortality was 2035 days (95% confidence interval [CI], 294‐4380 days); MST for disease‐specific mortality was not reached. Conclusions and Clinical Importance Approximately one‐third of cats with hypoadrenocorticism had hypercalcemia. In some cases, hyponatremia and hyperkalemia were not observed. Cats with nonneoplastic associated hypoadrenocorticism that survive initial hospitalization can have a favorable long‐term prognosis. Testing for EPI may be warranted in cats with hypoadrenocorticism.